Identification and validation of quantitative trait loci for chlorophyll content of flag leaf in wheat under different phosphorus treatments - Yang, Bin; Chen, Nan; Dang, Yifei; Wang, Yuzhi; Wen, Hongwei; Zheng, Jun; Zheng, Xingwei; Zhao, Jiajia; Lu, Jinxiu; Qiao, Ling (Frontiers in Plant Science, 2022)
Phosphorus deficiency is one of the most crucial abiotic stress factors affecting wheat yield formation. Chlorophyll content in flag leaves is closely related to the degree of phosphorus stress. Identifying major genes/loci associated with chlorophyll content in flag leaves under different phosphorus conditions is critical for breeding wheat varieties resistant to low phosphorus. Under normal, medium, and low phosphorus conditions, the chlorophyll content of flag leaves was investigated by a double haploid (DH) population derived from a cross between Jinmai 47 and Jinmai 84 in different filling periods. The chlorophyll content of the DH population and their parents decreased gradually during the S1-S3 period and rapidly during the S4 period. During the S1 and S2 periods, there was no statistically significant change in chlorophyll content between DH populations under three phosphorus conditions. However, in the S3 and S4 stages, the chlorophyll content of the DH population under low phosphorus was significantly lower than under normal phosphate conditions. Using a wheat 15K single-nucleotide polymorphism (SNP) panel, 157 QTLs associated with flag leaf chlorophyll content were identified. Their contributions to phenotypic variation explained (PVE) ranged from 3.07 to 31.66%. In normal phosphorus, medium phosphorus, and low phosphorus conditions, 36, 30, and 48 QTLs were found, respectively. Six major QTLs Qchl.saw-2B.1, Qchl.saw-3B.1, Qchl.saw-4D.1, Qchl.saw-4D.2, Qchl.saw-5A.9 and Qchl.saw-6A.4 could be detected under multiple phosphorus conditions. Different from previously reported chlorophyll loci, Qchl.saw-4D.1, Qchl.saw-4D.2, and Qchl.saw-6A.4 were revealed to be novel major QTLs. Furthermore, the closely linked SNP markers of Qchl.saw-4D.1 and Qchl.saw-4D.2 were validated as KASP markers in a DH population sharing the common parent Jinmai 84, which showed extreme significance (P<0.05) in more than three environments. In addition, both Qchl.saw-4D.1 and Qchl.saw-4D.2 were detectable under low phosphorus conditions and contributed up to 31.66% to the phenotypic, which has the potential to be utilized in molecular marker-assisted breeding for low phosphorus tolerance in wheat.